A γ-cyclodextrin-based metal–organic framework (γ-CD-MOF): a review of recent advances for drug delivery application. (21st April 2022) - Hamedi, Asma; Anceschi, Anastasia; Patrucco, Alessia; Hasanzadeh, Mahdi
Abstract: The relatively new class of porous material known as metal-organic framework (MOF) exhibits unique features such as high specific surface area, controlled porosity and high chemical stability. Many green synthesis approaches for MOFs have been proposed using biocompatible metal ions and linkers to maximise their use in pharmaceutical fields. The involvement of biomolecules as an organic ligand can act promising because of their biocompatibility. Recently, cyclodextrin metal–organic frameworks (CD-MOFs) represent environmentally friendly and biocompatible characteristics that lead them to biomedical applications. They are regarded as a promising nanocarrier for drug delivery, due to their high specific surface area, high porosity, tuneable chemical structure, and easy fabrication. This review focuses on the unique properties of CD-MOF and the recent advances in methods for the synthesis of these porous structures with emphasis on particle size. Then, the state-of-the-art drug delivery systems with various drugs along with the performance of CD-MOFs as efficient drug delivery systems are presented. Particular emphasis is laid on researches investigating the drug delivery potential of γ-CD-MOF.